Using of Nuclear Track Detector CR-39 To Measure Depleted Uranium Concentration of Mother's Milk. (Baghdad Science Journal, 2004)
Biological samples of mother's milk were collected from Iraqi southern provinces(Basrah,Messan,al-Muthana,Thikar)and Baghdad province to measure uranium concentration of the samples by using track technique of fission fragments as a result from uranium atom fission with thermal neutrons from neutrons source 24 I Am-Be with activity 16Ci and neutron flux of 5000 n/cm2.s on using nuclear track detector CR-39 It was found that the high percentage of depleted uranium concentration on the samples from Muthana province , which accounted as 4.183ppm therefore the samples was taken from the provinces (Thikar,Basrah,Baghdad),which was accounted the depleted uranium concentration as following (1.243,2.172,2.875) ppm respectively, with appear a small concentration percentage in the Messan province which was accounted (0.230)ppm .Although, this concentration was been on the one baby food menu from mother's milk nutrition.ln this research,the concentration of some essential trace elements in human breast milk, Ca, Na, K, Mg, Fe, Cu, Mn, Zn, Cr, Pb, Cd, Hg,was measured in the samples was taken from the above provinces by using atomic absorption technique and the result was indicated appear change in the concentration of the elements of the samples.